2008
DOI: 10.1093/eurheartj/ehn208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of right ventricular dysfunction in patients with haemodynamically stable pulmonary embolism: a systematic review

Abstract: RV dysfunction assessed by CT, echocardiography, or by cardiac biomarkers are all associated with an increased risk of mortality in patients with haemodynamically stable PE. These findings should be interpreted with caution because of the clinical and methodological diversity of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
325
2
52

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(403 citation statements)
references
References 22 publications
17
325
2
52
Order By: Relevance
“…6 In the above-mentioned meta-analysis of two studies (with two different RV/LV ratio thresholds, 1.5 and 1.0) including 191 normotensive patients with PE, a 58% (95% CI, 51---65%) overall negative and a 57% positive (95% CI, 49---64%) value of RV dilatation were reported on MDCT for predicting early death, yielding a relative risk for in-hospital mortality of 2.28 (95% CI, 0.9---5.9). 13 Our study extends these findings to a population of severely ill patients (all with RV/LV ratio >1.0) and demonstrates that patients with RV/LV ratio >1.8 have an 11-fold higher risk of mortality during medium-term follow-up. These results are comparable to those reported by Ghuysen et al, 14 in which patients with a mean RV/LV ratio of 1.52 had a mortality of 25%.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…6 In the above-mentioned meta-analysis of two studies (with two different RV/LV ratio thresholds, 1.5 and 1.0) including 191 normotensive patients with PE, a 58% (95% CI, 51---65%) overall negative and a 57% positive (95% CI, 49---64%) value of RV dilatation were reported on MDCT for predicting early death, yielding a relative risk for in-hospital mortality of 2.28 (95% CI, 0.9---5.9). 13 Our study extends these findings to a population of severely ill patients (all with RV/LV ratio >1.0) and demonstrates that patients with RV/LV ratio >1.8 have an 11-fold higher risk of mortality during medium-term follow-up. These results are comparable to those reported by Ghuysen et al, 14 in which patients with a mean RV/LV ratio of 1.52 had a mortality of 25%.…”
Section: Discussionsupporting
confidence: 71%
“…This is reflected by the low mean RV/LV ratios reported in the literature, ranging from 1.1 5,11 to 1.32. 12,13 Moreover, the proportion of patients undergoing thrombolytic therapy in these studies was also low.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Meta-analysis of five prospective studies of hemodynamically stable PE demonstrated that 44% of patients had RV dysfunction and a higher mortality rate with a sensitivity of 70%, a positive predictive value of 58%, and a negative predictive value of 60% for prediction of mortality [12]. In another study, the prognostic value of echocardiogram in hemodynamically stable PE patients was moderate [13]. In our study, 29% of patients had RV dysfunction, of which about (82%) belonged to long LOS group.…”
Section: Discussionmentioning
confidence: 99%
“…45 A recent meta-analysis has also confirmed this association. 46 Brain natriuretic peptides (BNPs) and N-terminal proBNP (NT-proBNP) are specific markers of stress on ventricular wall. A strong correlation exists between levels of these markers and RV dysfunction assessed by echocardiography.…”
Section: Risk Assessment and Stratificationmentioning
confidence: 99%